Reproductive disorders and obstetric complications in gynecological diseases - A L Unanian (Гинекология, 2018)
This publication examines the existing risks of obstetric complications and other reproductive disorders in women with gynecological diseases. The paper also discusses the issues of the pre-school training of women with gynecological diseases, with special emphasis on the use of dipyridamole, due to its pleiotropic action.